Efektivitas model pembelajaran matematika berbasis kinerja di Perguruan Tinggi - Hisyam Ihsan; Ahmad Zaki (Seminar Nasional LP2M UNM, 2019)
This study aims to determine the effectiveness of performance-based mathematics learning models in universities. The type of research used is experimental research, which is a comparison of performance-based mathematics learning models as experimental classes and direct learning models as a control class. The population in the study were mathematics department students of FMIPA UNM and the study sample was A1 education class as the experimental class and A2 education class as the control class. The data used in the study is the value of learning outcomes given after the completion of learning. The data analysis technique used is descriptive statistics and inferential statistics using variance analysis (ANOVA). The results showed that the value of the mathematics learning outcomes of the experimental class using a performance-based mathematics learning model was in the very high category, the value of the results of the mathematics control class using the direct learning model was in the medium category. The results of hypothesis testing show that performance-based mathematics learning is effective for use in college.